Life cycle assessment based method for the environmental and mechanical evaluation of waste tire rubber concretes - Masoud Bakhtiari Ghaleh; Payam Asadi; Mohammad Reza Eftekhar (Scientific Reports)
Abstract The utilization of waste tire rubber (WTR) in concrete is an environmentally sustainable solution that has garnered significant interest in recent years. However, incorporating WTR in concrete can lead to a reduction in its mechanical properties. This study proposes a life-cycle assessment-based method for the simultaneous evaluation of the environmental and mechanical aspects of WTR concrete. This method converts the generated environmental impacts into scores and defines a series of scenarios that employ pre-coating techniques to enhance the mechanical properties of WTR concrete. The assessment results using the proposed method reveal that, although incorporating WTR into concrete significantly reduces mechanical strength, it can also substantially decrease environmental impacts-by up to 75%-compared to the scenario of using ordinary concrete combined with waste rubber landfilling. Although the use of resin to increase the mechanical properties of rubber concrete increases the environmental pollutions, the improved concrete has lower environmental impacts compared to the base scenario. To evaluate the overall improvement, a total improvement coefficient is calculated, taking into account both the environmental scores and the compressive strength of the concrete. It is observed that the benefits of incorporating WTR in concrete outweigh the drawback of reduced compressive strength. The total improvement coefficient for waste tire rubber concrete reaches up to 1.7 and 2.35 when pre-coating with resins and incorporating 5% micro silica, respectively. The results were compared with those of previous studies and demonstrated that the proposed pre-coating method not only enhances concrete strength but also provides greater environmental benefits. This is because low-emission materials were used for strengthening, while high-emission WTR was incorporated into the concrete, reducing its overall environmental impact.